Challenges of Strengthening Culture in the Development of Sustainable Tourism Villages in Bali - Prasiasa, Dewa Putu Oka; Ni Wayan Karmini; Dewa Ayu Diyah Sri Widari (Institut Seni Indonesia Denpasar, 2024)
The development of a village into a sustainable tourism village is expected to be able to optimally meet cultural sustainability indicators. To realize cultural sustainability in the development of tourism villages in Bali, there are still challenges in strengthening culture such as the dynamics of authenticity and commodification, tourism political domination and hegemony, as well as strengthening traditional institutions. In order to increase the competitiveness of tourism, especially from the pillar of sustainable tourism villages, aspects of authenticity and commodification can increase their contribution to the local and national economy through the implementation of internationalization, traditionalization, and sacred versus profane; aspects of tourism political domination and hegemony through the implementation of policies related to the development of tourism villages; and aspects of strengthening traditional institutions through involving all levels of village society and community institutions in the village in relation to supporting the development of culture-based tourism villages, as well as revitalizing groups (sekaha-sekaha) that produce creative work to strengthen the development of tourism products in tourism villages and strengthen the image of a tourism village.